Aplicação de bordado computadorizado e estamparia têxtil em vestidos de noiva com menor custo: para casamentos diurnos - Yamamoto, Jenyfer Ketlen dos Santos (2015)
This academic paper presents a study on the bridal gown directed the wedding day, using cotton as a way to reduce the cost of raw materials and the application of surface techniques as a means of product differentiation. The wedding dress is sought after by women of different classes and cultures that need specific outfits for these special ceremonies. This study looks at the relationship of women with the bridal gown, analyzing their choices and perceptions related to fashion, body and style. Through literature, tries to show one of the oldest traditions, still in use, conceptualize wedding fashion, describing fabrics, prints, embroideries, textures and through field research to identify an audience.